Correlation of Fitness Levels with Physical Activity in Elderly Patients in Yogyakarta, Indonesia - Nurhayati, Ummy A'isyah; Laksono, Tri; Hasnawati, Baiq Nurul (Jurnal Keterapian Fisik, 2024)
Background: Fitness is closely linked to aerobic capacity, which depends on the availability of oxygen to meet the needs of the blood and facilitate the burning process to provide energy to maximise the performance of the body's organs. Under certain conditions, such as disabilities, reduced function, or certain diseases that prevent physical activity, especially in the elderly, the aerobic process may not function optimally. This study investigates the correlation between fitness level and physical activity in elderly patients at the Muhammadiyah Community Welfare Development Hospital (RS PKU) in Bantul, Yogyakarta. Methods: The research design is cross-sectional, using purposive sampling. To assess fitness and physical activity levels, the six-minute walk test (6MWT) and the Global Physical Activity Questionnaire (GPAQ) were used in the study. Thirty-six (36) responded to the questionnaires and participated in the study. The analysis of the data was performed using the Spearman rank correlation test. Results: The Pearson correlation test showed that there was a significant correlation (r = 0.657** and p-value = 0.000) between fitness level and physical activity. Conclusion: There is a strong correlation between fitness level and physical activity in elderly patients at PKU Muhammadiyah Bantul.